Exfoliation syndrome in Northern Nigeria - Idakwo U (Dove Medical Press, 2018)
Ugbede Idakwo,1 Olusola Olawoye,2 Benedictus GK Ajayi,1 Robert Ritch3 1Eleta Eye Institute, Ibadan, Nigeria; 2Department of Ophthalmology, College of Medicine, University of Ibadan, Ibadan, Nigeria; 3Einhorn Clinical Research Center, Department of Ophthalmology, New York Eye and Ear Infirmary of Mount Sinai, New York, NY, USA Purpose: To estimate the frequency of exfoliation syndrome (XFS) and its association with ocular diseases in Northern Nigeria.Materials and methods: Consecutive patients who presented to the outpatient department of ECWA Eye Hospital Kano from February 2015 to May 2015 were included in the study. Each patient had a complete ophthalmic examination. The anterior segment examination included tonometry, gonioscopy, and detailed slit-lamp examination to assess for the presence or absence of exfoliation material, inflammatory cells, and other abnormal findings. Patients with exfoliation material on the anterior lens surface and/or pupillary margin in either or both eyes were considered to have XFS. Statistical analysis was performed using the Statistical Package for the Social Sciences version 16.0.Results: A total of 620 patients living in Northern Nigeria from the 6 geopolitical zones were examined. The majority of them (34.5%) were indigenous Hausas. There was a male preponderance of 56.6%, while the mean age at presentation for examination in all age groups was 55.7±13.7 years. There were 9 patients with XFS; the frequency was 1.5%, with most of the patients being 70–80 years old. In patients who were ≥50 years, the frequency was 2.5%. Patients with XFS had a higher mean age of 68±4.9 years. The frequency of XFS among glaucoma patients was 4.4%, while among cataract patients it was 3.7%. No other associated ocular disease was found in the patients with XFS.Conclusion: This study shows that XFS does exist in Northern Nigeria, as was found in the South. The prevalence of XFS was, however, not reported in the Nigerian National Blindness and Visual Impairment Survey. Therefore, a population-based study is still needed to determine the true prevalence of XFS in Northern Nigeria. Keywords: exfoliation syndrome, glaucoma, cataract, Northern Nigeria, intra-ocular pressure